Single nucleotide polymorphism and bioinformatics analysis of DQA2 gene in yak - LI Zhuo; CHEN Lang; JIANG Tao; LIU Lixia; ZHANG Li; WANG Rui; LI Yaodong (浙江大学学报. 农业与生命科学版)
Single nucleotide polymorphism (SNP) of DQA2 gene in yak was analyzed via genomic DNA pooled amplification and directly sequencing, and further the influence of SNP sites on the secondary structures of mRNA and protein of DQA2 gene were predicted and analyzed by bioinformatic software. The results showed that the polymorphism of DQA2 gene in yak was high, and 14 SNP sites were detected. Only one SNP site was located on the intron 1, while 13 SNP sites were located on exon regions. Nine SNP sites were missense mutations, which resulted in changes in corresponding amino acids. The results of secondary structure prediction showed that eight SNP sites increased the stability of secondary structure of mRNA, and four SNP sites reduced the stability of secondary structure of mRNA. The SNP sites of missense mutation changed the secondary structure of DQA2 protein in yak. The proportion of random coil was the highest, followed by extended strand, and β-turn was the lowest among components of protein secondary structure before and after mutation. The results can provide basic data for further research on yak major histocompatibility complex (MHC) gene and theoretical basis for screening the molecular markers of yak disease resistance.